Digital Preservation of Photo Journalism (Case Study of the Kompas Daily) - Rahmawati, Yuli (Record and Library Journal, 2015)
Newspaper provides many information from politics, economics, cultures, and sports for society. Newspaper reports important events in the world. Besides the news, there also some pictures portraying those events. So readers will easilly to see what happen visually. According to the journalistic concept, photos has comply as a reference source. Kompas daily, firstly published on 1965, and published many historical photos both paper and digital format. The digitize process is done by kompas information center, through scanning, indexing, and syncronizing. Two most important issues are standardization of metadata and integrated retrieval systems. Standarization of metadata was design based on publishing standard,Â  IIM and was modified with IPTC news codes. Information retrieval systems was built by inserting information about publication. This system connecting photo creating data, storage systems, and retrieval systems. For kompas daily, the availability if digital objectÂ  such as photo can trigger the innitiatives of re-publishing historical momments in thematical rubrics. Digitize will give benefits for information disemination.